University students' understanding and options of eating disorders: A qualitative study. (20th October 2021) - Manning, M; Greenfield, S
Abstract: Background: Eating disorders (EDs) affect 1.25 million people in the UK. Evidence suggests the public perceive EDs as a female issue and display stigma and poor mental health literacy (MHL) towards EDs. There is a high prevalence of EDs in university populations, so it is important to determine the MHL of this at-risk group. Qualitative research exploring the MHL of this population is incomplete. Aims: To explore university students' beliefs and opinions of EDs, their knowledge of symptoms, treatment and help sources and how these are influenced by biological sex. Methods: A qualitative study, using semi-structured interviews with seven male and seven female participants. Interviews were analysed using inductive thematic analysis. Analyst triangulation and member validation occurred. Results: Analysis revealed six themes, each with subthemes: ED characteristics, causes, body image, seeking help, stigma and awareness. Students displayed poor awareness towards ED signs and symptoms, causes and help sources. Students were not stigmatising towards EDs, but many perceived them as a female problem and believed society to be stigmatising. Many referenced informal sources of information such as social media and expressed a desire for ED teaching. Sex did not have a significant influence on knowledge or opinions of EDs in this study, however there were some differences, for example some males were more likely to see EDs as a weakness and to perceive themselves as having low levels of knowledge. Conclusions: University students show poor awareness of certain aspects of ED-MHL including help sources and symptom recognition. Although students were not stigmatising of EDs themselves, many perceived high levels of public stigma. This, alongside poor knowledge, may delay help-seeking. Campaigns educating students and the public about EDs would aid earlier diagnosis, improving long-term outcomes. Further research into awareness and knowledge in other populations would be beneficial. Key messages: University students interviewed perceived high levels of public stigma around eating disorders, although not stimatising themselves. Campaigns educating students and the public about EDs would aid earlier diagnosis, improving long-term outcomes.